Innovative Work Behavior: The Role of Job Crafting and Job Autonomy Mediated by Work Engagement - Joshua Nathaniel; Yustina Erti Pravitasmara Dewi (Petra International Journal of Business Studies, 2024)
This research aimed to determine the effect of job crafting and job autonomy on innovative work behavior mediated by work engagement.  It was conducted at a banking company in Semarang, Central Java.  Respondents were selected from which company using a non-probability sampling technique, namely saturation sampling.  An online questionnaire was distributed to 100 workers with permanent employee statuses. This study took a quantitative approach, where the data analysis was undertaken using the PLS-SEM method in SmartPLS 4. The results show that (i) Job autonomy has a positive and significant effect on innovative work behavior, while job crafting does not significantly affect innovative work behavior. (ii) Work engagement does not mediate the influence of job autonomy on innovative work behavior, but it fully mediates the influence of job crafting on innovative work behavior.